Comparing Hedging Effectiveness: An Application of the Encompassing Principle - Dwight R. Sanders; Mark R. Manfredo (Journal of Agricultural and Resource Economics, 2004)
An empirical methodology is developed for statistically testing the hedging effectiveness among competing futures contracts. The presented methodology is based on the encompassing principle, widely used in the forecasting literature, and applied here to minimum variance hedging regressions. Intuitively, the test is based on an alternative futures contract's ability to reduce residual basis risk by offering either diversification or a smaller absolute level of basis risk than a preferred futures contract. The methodology is easily extended to cases involving multiple hedging instruments and general hedge ratio models. Empirical applications suggest that the encompassing methodology can provide information beyond traditional approaches of comparing hedging effectiveness.